Pengembangan Media Pembelajaran EBOP (Explosions Box of Physics) untuk Meningkatkan Minat Belajar Siswa - Ana Septiani Mutiah; Arini Rosa Sinensis; Siti Anisatur Rofiqah (Pendidikan Fisika Universitas Nurul Huda, 2022)
The aims of this study were: 1) to develop and produce EBOP (Explosions Box of Physics) media to increase students' interest in learning about Free Falling in Class X High School; 2) Knowing the feasibility of EBOP (Explosions Box of Physics) media to increase students' interest in Free Falling in Class X High School. This research is a Research and Development (R&D) with the ADDIE development model (analyze, design, development, implementation, and evaluation). The subjects of this study were two media expert validators and 2 material expert validators as well as 34 students in class X IPA 2 for the 2021/2022 academic year. The technique of collecting data uses assessment sheets of media experts and material experts as well as student learning interest questionnaires. The results of this study indicate that: 1) EBOP (Explosions Box of Physics) learning media is suitable for use in free fall learning, the validation value obtained from media experts is 0.88 in the high category and the validation value obtained from material experts is 0. 85 high validation categories; 2) The results of increasing student interest in learning use the N-Gain formula with a value of 0.32 which indicates the medium category.